ANALYSIS OF COGGING TORQUE REDUCTION FROM DESIGN COMPUTATIONAL PERMANENT MAGNET SYNCHRONOUS MOTOR WITH TAGUCHI METHOD - Wahyuni, Fitri; Julian, James; Ferdyanto, Ferdyanto; Fauzi, Ade Fikri (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Permanent Magnet Synchronous Motor (PMSM) applications include electric vehicles, industrial pumps, wind turbines, aerospace technology, and many others. In this study, cogging torque is the central aspect of the discussion, which is the motor model, the thickness of the permanent magnet rotor, and the air gap in the electric motor influence. The Taguchi method uses parameter levels on the motor, which are divided into 16 types of orthogonal arrays, where the process is carried out twice in iterations. The first stage of simulation testing was to produce the primary model where number 4 (A1B4 series) was obtained as the most optimal motor model with a cogging torque of 1.56 Nm and an air gap flux density of 768 mTesla (mili tesla). Then the second test was to modify several parts of the motor with the following 16 orthogonal array types, which produced number 8 (A2B4 series) with a cogging torque of 1.08 Nm and an air gap flux density of 733 mTesla. One of the parameters apart from the cogging torque must be maintained is the air gap flux density. This variable affects the permeability of the motor so that later it will affect the amount of material used and the production costs of electric motors. The final result is a model that produces the lowest cogging torque while maintaining other parameters on the motor.